Explaining the Czech Foreign Policy Towards China (1992-2017) - Adamková, Petra; Garlick, Jeremy; Havlová, Radka, 1975-; Vysoká škola ekonomická v Praze. Fakulta mezinárodních vztahů (2017)
The presented master´s thesis aims to explain the Czech foreign policy towards China since 1992 to the year 2017. In order to analyse the approach, the author firstly carries out a literature review and introduces three levels of foreign policy analysis, i.e. system, (sub)state and individual. Key relevant phenomena are introduced and the stage is set for the case study. The empirical part of the presented thesis begins with a summary of the foreign policy of the Czech Republic towards the People´s Republic of China. To provide a complex picture, the Chinese interests in Czechia are described as well. The last chapter represents the analysis itself. The notion of polarity and great powers in the system level, the national attributes with domestic influences, and the personalities of two presidents provide the basic aspects contributing to the final explanation.
Vedoucí práce: Jeremy Alan Garlick
Diplomová práce (Ing.)—Vysoká škola ekonomická v Praze. Fakulta mezinárodních vztahů, 2017
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2017
Způsob přístupu: Internet
Keywords: international and diplomatic studies [obor dipl. práce]; diplomové práce; master's theses